2014
DOI: 10.3389/fnsys.2014.00015
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric pallidal neuronal activity in patients with cervical dystonia

Abstract: The origin of asymmetric clinical manifestation of symptoms in patients suffering from cervical dystonia (CD) is hitherto poorly understood. Dysregulated neuronal activity in the basal ganglia has been suggested to have a role in the pathophysiology of CD. Here, we re-assessed the question to what extent relative changes occur in the direct vs. indirect basal ganglia pathway in CD, whether these circuit changes are lateralized, and how these alterations relate to CD symptoms. To this end, we recorded ongoing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 81 publications
(146 reference statements)
5
60
1
3
Order By: Relevance
“…Micro-tip impedances were 0.8 ± 0.1 MOhm (range 0.5e1.0). Starting at 10 mm above the surgical target, electrodes were advanced in steps of 500 mm and ongoing activity was recorded at each site for at least 20 s. In agreement with previous observations [12], under general anaesthesia with propofol/remifentanil, unit activity in both pallidal segments was often indistinguishable and characterized by a multitude of different activity levels and patterns, respectively. Therefore, the occasional recording of highly regular "border cell" discharges at 20e30 Hz proved to be especially helpful for a delineation of peri-pallidal white matter layers and for an on-line differentiation between the GPe and GPi, respectively.…”
Section: Methodsmentioning
confidence: 61%
“…Micro-tip impedances were 0.8 ± 0.1 MOhm (range 0.5e1.0). Starting at 10 mm above the surgical target, electrodes were advanced in steps of 500 mm and ongoing activity was recorded at each site for at least 20 s. In agreement with previous observations [12], under general anaesthesia with propofol/remifentanil, unit activity in both pallidal segments was often indistinguishable and characterized by a multitude of different activity levels and patterns, respectively. Therefore, the occasional recording of highly regular "border cell" discharges at 20e30 Hz proved to be especially helpful for a delineation of peri-pallidal white matter layers and for an on-line differentiation between the GPe and GPi, respectively.…”
Section: Methodsmentioning
confidence: 61%
“…Im GPe von Patienten mit segmentaler bzw. fokaler zervikaler Dystonie findet man ein vergleichbares Aktivitätsniveau [30,45,50]. In der Grenzlamelle am Übergang zum GPi registriert man wieder die Aktivität von Grenzzellen (siehe oben).…”
Section: Neuronale Aktivität Oberhalb Des Gpi: Striatum Medulläre Grunclassified
“…In der englischsprachigen Literatur werden diese Zellen als ,,high frequency discharge neurons" bezeichnet. Die mittlere Entladungsrate von Nervenzellen im posteroventrolateralen GPi von Parkinsonpatienten ist mit 70-90 Hz [8,18,19,27,29,45,50,53,56] deutlich höher als die durchschnittliche Aktionspotential-Frequenz im GPi von Patienten mit Dystonie (50-70 Hz) [30,45,50,56]. Der Unterschied in der Entladungsrate zwischen GPe und GPi kann bei iMEA im Pallidum von Patienten mit Morbus Parkinson die Differentialdiagnose zwischen beiden Kerngebieten erleichtern [29].…”
Section: Spontanaktivität Im Gpiunclassified
See 1 more Smart Citation
“…In one study, Moll et al (2014) recorded single cell as well as local field potential activity from globus pallidus (internal and external segments) in patients with cervical dystonia undergoing deep brain stimulation. They found that cervical dystonia is associated with asymmetric pallidal functions.…”
Section: Human Studiesmentioning
confidence: 99%